2002
DOI: 10.1037/0894-4105.16.3.309
|View full text |Cite
|
Sign up to set email alerts
|

Commonalities and differences in the working memory components underlying letter and category fluency tasks: A dual-task investigation.

Abstract: This study used a dual-task interference paradigm to test the hypothesis that different subcomponents of working memory differentially contribute to performance on letter fluency and category fluency tasks. College students (N = 96) performed each type of verbal fluency task in isolation and concurrently with I of 3 secondary tasks. The secondary tasks were chosen for their putative involvement in different working memory subcomponents. Two subsystems of working memory, the phonological loop and the visuospati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
96
0
2

Year Published

2005
2005
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 157 publications
(111 citation statements)
references
References 43 publications
12
96
0
2
Order By: Relevance
“…Thus, only the candidate three-factor correlated model seems to provide an adequate fit to the data. However, after an examination of the residuals, a working memory  letter fluency link was added to this model in view of a potential increment in fit and, even more importantly, considering that the letter-fluency tasks is known to require working memory resources (e.g., Rende, Ramsberger & Miyake, 2000).…”
Section: Resultsmentioning
confidence: 99%
“…Thus, only the candidate three-factor correlated model seems to provide an adequate fit to the data. However, after an examination of the residuals, a working memory  letter fluency link was added to this model in view of a potential increment in fit and, even more importantly, considering that the letter-fluency tasks is known to require working memory resources (e.g., Rende, Ramsberger & Miyake, 2000).…”
Section: Resultsmentioning
confidence: 99%
“…The choice RT task effects were also considered separately for the letter fluency and the category fluency tasks. According to Rende et al (2002), if response selection is mediated by a subsidiary component of WM, the choice RT task should differentially affect letter and category fluency performance. However, we observed that the decrement in fluency performance due to the concurrent choice reaction task was similar for the different variants of the fluency task.…”
Section: Discussionmentioning
confidence: 99%
“…First, if response selection involves executive control, a concurrent choice reaction task should have a more disruptive effect on a task that requires many executive resources (i.e., verbal fluency) than does concurrent simple reaction. The second prediction refers to the processing differences between letter and category fluency, as reported by Rende et al (2002). If response selection is not mediated by verbal or spatial processing, the choice RT task is predicted not to differentially affect letter and category fluency.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations